2017
DOI: 10.3747/co.24.3684
|View full text |Cite
|
Sign up to set email alerts
|

The Framingham Risk Score Underestimates the Risk of Cardiovascular Events in the HER2-Positive Breast Cancer Population

Abstract: IntroductionPatients with breast cancer (bca) who overexpress her2 (the human epidermal growth factor receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Most prior studies on CVD after EBC have focused on older women, specific treatments, or specific types of CVD, limiting direct comparisons to our data (3,5,11,12,32,49). It was recently reported that the Framingham risk score underestimates CVD risk in HER2-positive breast cancer (50). This may reflect the higher CVD rate in cardiotoxin-treated patients compared with cancer-free women.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies on CVD after EBC have focused on older women, specific treatments, or specific types of CVD, limiting direct comparisons to our data (3,5,11,12,32,49). It was recently reported that the Framingham risk score underestimates CVD risk in HER2-positive breast cancer (50). This may reflect the higher CVD rate in cardiotoxin-treated patients compared with cancer-free women.…”
Section: Discussionmentioning
confidence: 99%
“…In our analyses, we used the non-laboratory-based Framingham risk measure, an estimate of 10-year general CVD risk that integrates information on age, diabetes, smoking, BMI, and treated and untreated systolic blood pressure, to compare changes in risk according to breast cancer status. Though this risk score has not been validated among women with breast cancer, and may underestimate the absolute risk in this population since it does not incorporate information on a woman’s history of cardiotoxic cancer treatments, 14 it is useful as a summary measure of traditional risk factors that may increase CVD risk in both cancer and noncancer groups. To our knowledge, ours is the first study among breast cancer survivors to utilize the non-laboratory-based version of the Framingham risk score, which, unlike the full Framingham risk model, uses BMI rather than lipids in the estimation of CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of risk scores are available for the prediction of coronary heart disease such as the Framingham risk score (FRS) [ 20 , 21 ], World Health Organization/International Society of Hypertension (WHO/ISH) risk prediction charts [ 38 ], American College of Cardiology/American Heart Association (ACC/AHA) pooled cohort equations [ 36 ], the third Joint British Societies’ risk calculator (RiskJBS) [ 37 ], and the Systematic Coronary Risk Evaluation (SCORE) [ 39 ]. While these are validated and widely used tools for the prediction of coronary heart disease, studies suggest that they tend to underestimate an individual’s actual risk, thereby potentially delaying initiation of an appropriate intervention such as lifestyle modification [ 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Risk Scores and Lifestyle Behavioursmentioning
confidence: 99%